The passion and the passionalization in "Saudosa maloca" - Coelho, Márcio (Laboratório Editorial FCL-UNESP, 2008)
In this work we propose a paraphrase of Algirdas Julien Greimas “De la Nostalgie – Étude de Sémantique Lexicale” based on the song “Saudosa Maloca”, composed by Adoniran Barbosa. We also talk about the compatibility between the melodic syntax and the passional organization of the song’s content.